Mechanical properties of Fe rich Fe–Si alloys: ab initio local bulk-modulus viewpoint. (17th November 2017) - Kr Bhattacharya, Somesh; Kohyama, Masanori; Tanaka, Shingo; Shiihara, Yoshinori; Saengdeejing, Arkapol; Chen, Ying; Mohri, Tetsuo
Abstract: Fe-rich Fe–Si alloys show peculiar bulk-modulus changes depending on the Si concentration in the range of 0–15 at.%Si. In order to clarify the origin of this phenomenon, we have performed density-functional theory calculations of supercells of Fe–Si alloy models with various Si concentrations. We have applied our recent techniques of ab initio local energy and local stress, by which we can obtain a local bulk modulus of each atom or atomic group as a local constituent of the cell-averaged bulk modulus. A2-phase alloy models are constructed by introducing Si substitution into bcc Fe as uniformly as possible so as to prevent mutual neighboring, while higher Si concentrations over 6.25 at.%Si lead to contacts between SiFe8 cubic clusters via sharing corner Fe atoms. For 12.5 at.%Si, in addition to an A2 model, we deal with partial D03 models containing local D03-like layers consisting of edge-shared SiFe8 cubic clusters. For the cell-averaged bulk modulus, we have successfully reproduced the Si-concentration dependence as a monotonic decrease until 11.11 at.%Si and a recovery at 12.5 at.%Si. The analysis of local bulk moduli of SiFe8 cubic clusters and Fe regions is effective to understand the variations of the cell-averaged bulk modulus. The local bulk moduli of Fe regions become lower for increasing Si concentration, due to the suppression of bulk-like d – d bonding states in narrow Fe regions. For higher Si concentrations till 11.11 at.%Si, corner-shared contacts or 1D chains of SiFe8 clusters lead to remarkable reduction of local bulk moduli of the clusters. At 12 at.%Si, on the other hand, two- or three-dimensional arrangements of corner- or edge-shared SiFe8 cubic clusters show greatly enhanced local bulk moduli, due to quite different bonding nature with much stronger p - d hybridization. The relation among the local bulk moduli, local electronic and magnetic structures, and local configurations such as connectivity of SiFe8 clusters and Fe-region sizes has been analyzed. The ab initio local stress has opened the way for obtaining accurate local elastic properties reflecting local valence-electron behaviors.